2008
DOI: 10.1007/s10549-008-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of the triple-negative tumors in Chinese breast cancer patients

Abstract: In order to analyze the clinicopathological features of Chinese triple negative tumors, we performed a retrospective study of 1993 female unilateral breast cancer patients undergoing surgery in Cancer Hospital of Fudan University, Shanghai, China. Survival curves were performed with Kaplan-Meier method and annual recurrence hazard was estimated by hazard function. We observed that the rate of larger tumors in triple negative patients was higher than that in HR+/ERBB2- women, but lower than that in ERBB2+ subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 56 publications
8
62
2
Order By: Relevance
“…Therefore, tumor subgroup (TNBC versus non-TNBC) was also a prognostic factor for 5-year OS or 5-year DFS in our study. This finding differs with some publications in Asian countries [7,16], but is consistent from reports from Western countries [20,21]. TNBC is characterized by distinct clinical features and genetic patterns, and this heterogeneity of TNBC may require different diagnostic and therapeutic interventions.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Therefore, tumor subgroup (TNBC versus non-TNBC) was also a prognostic factor for 5-year OS or 5-year DFS in our study. This finding differs with some publications in Asian countries [7,16], but is consistent from reports from Western countries [20,21]. TNBC is characterized by distinct clinical features and genetic patterns, and this heterogeneity of TNBC may require different diagnostic and therapeutic interventions.…”
Section: Discussionsupporting
confidence: 73%
“…Our data show that TNBC in Taiwan may have different prognostic factors and characteristics than the disease has in Western countries, possibly because of genetic heterogeneity. The incidence of TNBC in our population stands at 21.4%, which is higher than that reported in the literature [4,5,16]. In Japan, the triple-negative subtype accounts for 15.5% of breast cancers from surveillance data of the Registration Committee of the Japanese Breast Cancer Society, with a predominance of postmenopausal women [14].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Many oncologists believe that breast cancer is a clinically heterogeneous disease with different responses to therapy [1,2,3,4]. Of interest, some studies have suggested that adjuvant tamoxifen exhibits different effects on the lipid and liver profiles of cancer patients [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Liedtke et al (2008) reported that patients with triple-negative breast cancer had significant higher pathological complete remission (pCR) rate compared with non-triple-negative disease, whereas triplenegative breast cancer patients with residual disease (RD) after neoadjuvant chemotherapy had worse prognosis. Yin et al (2009) have recently reported that there were some dissimilarity between Chinese breast cancer patients and western population, which raises the question whether the triple-negative paradox (chemosensitive but poor survival) holds true in Chinese population. In this study, we used immunohistochemistry to classify tumor into TNBC and non-TNBC and examined the relationship between neoadjuvant chemotherapy response and long-term clinical outcome, including disease-free survival (DFS) and overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%